Analisis Kepuasan Konsumen Terhadap Sayuran Hydroponik Di Desa Kolursari Kecamatan Bangil Kabupaten Pasuruan - Puji Sirrun Nahar Muhammad (Lembaga Pengembangan Kinerja Dosen, 2023)
Omega Farm is a business engaged in agriculture and its business is selling hydroponic attributes. The research objective was to analyze consumer satisfaction with hydroponic vegetables. The basic method used is a quantitative descriptive analysis method. Sampling using interview method with a total of 30 respondents. This study uses primary and secondary data sources, primary data obtained from interviews, questionnaires, documentation and others. While secondary data obtained from related research. The research respondents are customers who often buy at Omega Farm, this study conducted validity and reliability tests using the help of SPSS version 25. The analytical method uses the CSI (Customer Satisfaction Index) results show that the level of customer satisfaction for hydroponic vegetables based on the calculated value of the Customer Satisfaction Index is 81.74 which is included in the satisfied category. The variables that gave the highest satisfaction were cleanliness, freshness of vegetables and packaging design.